SAT0620 Potential role of metacarpophalangeal joints ultrasound in the differential diagnosis between early rheumatoid arthritis and early spondyloarthritis. (15th June 2017) - Batticciotto, A; Prato, G; Antivalle, M; Ditto, MC; Gerardi, MC; Talotta, R; Atzeni, F; Sarzi-Puttini, P
Abstract : Background: Several studies have demonstrated that musculoskeletal ultrasound (MSUS) is more sensitive in diagnosing arthritis when compared to clinical examination, although, as underlined in a recent review, still remains controversial whether it can improve substantial discriminatory value in an early arthritis (EA) setting.(1) In 2011 Gutierrez M. et al. published preliminary data on high frequency of peritenon extensor tendon inflammation in Psoriatic arthritis (PsA) patients, suggesting a relevant potential role for US in differential diagnosis between Rheumatoid Arthritis (RA) and PsA at metacarpophalangeal (MCP) joints level and recommending additional research in order to confirm these data.(2) Objectives: To compare MSUS findings between early RA and early Spondyloarthritis (SpA) patients at MCP joints level. Methods: From a consenting cohort of EA patients presenting to our Rheumatology Department, we retrospectively selected 35 patients that within one year from the first visit had a defined diagnosis of RA (according with the 2010 ACR/EULAR criteria) or of axial/peripheral SpA (according with the 2009 ASAS criteria). Demographic, clinical parameters and MCPs' MSUS assessment at baseline were recorded during the patients' first EA clinic visit by an experienced Rheumatologist and by a blinded skilled sonographer. ESAOTE MyLAB 70 with 6–18 MHz linear array transducer was used for all patients scanning and US were scored according with OMERACT guidelines. Results: MSUS data of twenty RA patients (17 F – 3 M; median age of 59 yrs with range 35–83 yrs, median time for defined diagnosis of 2, 4 months with range 1–11 months) and 15 SpA patients (9F–6M; median age of 53 yrs with range 18–78 yrs, median time for defined diagnosis of 1, 7 months with range 1–8 months) were retrospectively analyzed. At the first EA clinic visit, all patients showed at least one joint with synovial fluid and/or synovial hypertrophy in Grey scale (GS) with a score >1 and no statistically significant differences were found in the percentage of patients that presented at least one joint with power Doppler (PD) positivity (55% RA Vs 53% SpA, p=0, 92) and that presented PD positivity tenosynovitis of the flexor tendons in at least one finger (10% RA Vs 33% SpA, p=0, 08). A statistically significant difference was found in the percentage of patients with erosions in at least one MCP (25% RA Vs 0% SpA, p=0, 036) and in the percentage of patients with PD positive paratenonitis of the extensor tendons in at least one finger (30% RA Vs 80% SpA pts, p=0, 003). Conclusions: Early RA patients showed a statistically higher percentage of erosions at MCPs' MSUS evaluation of the first visit of the EA clinic, when compared with early SpA group and early SpA patients presented at the level of the extensor tendons an higher percentage of PD positive paratenonitis when compared with the early RA group. References: Lage-Hansen PR. et al. The role of ultrasound in diagnosing rheumatoid arthritis, what do we know? An updated review. Rheumatol Int.2017Feb;37(2):179–187. Gutierrez M. et al. Differential diagnosis between rheumatoid arthritis and psoriatic arthritis: the value of ultrasound findings at metacarpophalangeal joints level.Ann Rheum Dis.2011 Jun;70. Disclosure of Interest: None declared